2011
DOI: 10.1055/s-0031-1280366
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Comparisons of Albiflorin and Paeoniflorin after Oral Administration of Shaoyao-Gancao-Tang and Single Herb Paeony Decoction to Rats

Abstract: Shaoyao-Gancao-Tang (SGT) is a traditional Chinese prescription containing Radix Paeoniae alba and Radix Glycyrrhizae and is commonly used to relieve pains. Albiflorin and paeoniflorin are the main effective compounds of Radix Paeoniae alba, and the pharmacokinetic differences of the two compounds in rats after oral administration of SGT and single herb Paeony decoction were studied. At different time points (5, 10, 15, 20, 30, 45, 60, 90, 120, 180, 240, 360, and 540 min) after administration, plasma concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…1). Previous studies have shown that paeoniflorin, an active component of Paeonia lactiflora, inhibits the activity of LPSinduced liver inflammatory reactions (Kim and Ha, 2010;Gan et al, 2012). Glycyrrhizin is a triterpenoid saponin glycoside of glycyrrhizic acid.…”
Section: Discussionmentioning
confidence: 99%
“…1). Previous studies have shown that paeoniflorin, an active component of Paeonia lactiflora, inhibits the activity of LPSinduced liver inflammatory reactions (Kim and Ha, 2010;Gan et al, 2012). Glycyrrhizin is a triterpenoid saponin glycoside of glycyrrhizic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In pharmacokinetic study, one or more active compounds as the targeted components are selected to represent the pharmacokinetic of entire extract and prescription due to the existence of too complex ingredients in traditional herbal medicines (Wu et al, 2009). Paeoniflorin is a major bio-active component in paeoniflorin-containing herbal medicines and their prescription such as Cortex Moutan, Radix Paeoniae, Samul-tang, Shaoyao-Gancao-Tang, Shuang-Dan and Tang-Min-Ling-wan and used as a representative compound in their pharmacokinetic study (Gan et al, 2012;Tong et al, 2010;Wu et al, 2009). In this respect, we selected paeoniflorin as a target compound.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…Xu et al [19, 20] compared pharmacokinetics of ten bioactive compounds in rat plasma after oral administration of different combinations ( Paeonia  : Glycyrrhiza , 1 : 1 or 1 : 4) of SGD and found that there were perceptible differences in pharmacokinetic parameters (Cmax, AUC 0- t , and CL) of the analytes except for liquiritin between the two groups. Albiflorin and paeoniflorin are the main effective compounds of Radix Paeoniae alba , and their pharmacokinetic differences in rats after oral administration of Shaoyao-Gancao-Tang (SGT) and single herb peony decoction were studied in Gan and coworkers' research [21]. The results indicated that some components in the other ingredient herbs of SGT ( Radix Glycyrrhizae ) had pharmacokinetic interaction with albiflorin and paeoniflorin and hence reduced their systematic exposure level.…”
Section: Modern Studies Of Sgd Compatibilitymentioning
confidence: 99%